2018
DOI: 10.1101/412064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Gradient of Microstructural Changes in Normal-Appearing White Matter in Tracts Affected by White Matter Hyperintensities in Older Age

Abstract: Brain white matter hyperintensities (WMH), common in older adults, may contribute to cortical disconnection and cognitive dysfunction. The presence of WMH within white matter (WM) tracts indicates underlying microstructural WM changes that may also affect the normal-appearing WM (NAWM) of a tract. We performed an exploratory study using diffusion magnetic resonance imaging of 52 healthy participants from the Lothian Birth Cohort 1936 (age 72.2 ± 0.7 years) selected to include a range of WMH burden, to quantify… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 65 publications
4
13
0
Order By: Relevance
“…We suggest our findings of the impact of tract-defined WMH on memory performance is partially explained by the previously proposed concept of “disconnection” (Lockhart et al., 2012; Munoz Maniega et al., 2019; O'Sullivan et al., 2001; Ritchie et al., 2015), which may mediate the effect of tract WMH on cognitive performance. Neuroimaging studies suggest that long-term memory is dependent on multiple cortical and subcortical regions, which are integrated via neural networks (Charlton et al., 2010; Grady et al., 2003; Ranganath et al., 2005).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We suggest our findings of the impact of tract-defined WMH on memory performance is partially explained by the previously proposed concept of “disconnection” (Lockhart et al., 2012; Munoz Maniega et al., 2019; O'Sullivan et al., 2001; Ritchie et al., 2015), which may mediate the effect of tract WMH on cognitive performance. Neuroimaging studies suggest that long-term memory is dependent on multiple cortical and subcortical regions, which are integrated via neural networks (Charlton et al., 2010; Grady et al., 2003; Ranganath et al., 2005).…”
Section: Discussionsupporting
confidence: 63%
“…Our unexpected finding regarding the relationship between WMH in projection white matter tracts, particularly the relationship between corticospinal tract and memory, deviates from previous DTI studies, which suggested a role of the corticospinal tract in sensorimotor functions rather than cognitive functions (Carter et al., 2012; Karahan et al., 2019). A plausible explanation of the relationship between corticospinal tract WMH and memory may simply be due to the tract's proximity to the lateral ventricles, where periventricular WMH reside and are known to be associated to memory (Munoz Maniega et al., 2019; Smith et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A study in 52 normal individuals at the beginning of the 8th decade of life observed that despite WMH having similar effects on tract infrastructure, whether they be intersecting or nearby, differences in tract water diffusion properties around WMH suggest that tract degeneration may propagate along the white matter tract for intersecting WMH, while in some areas of the brain there is a larger and more localized accumulation of axonal damage in tract tissue nearby a non-connected WMH. 47 This study also complements findings by other studies in smaller SLE samples, which found altered structural network parameters in SLE patients 13,14 compared to controls, with only few differences in functional hub measures. 14…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the adult pig and human brain are composed of 60% white matter, in contrast to <12% in the adult rat brain ( 5 ). This may be crucial for translation since white matter is more prone to develop edema and thus aggravates the pressure-induced trauma in the cerebrum ( 2 , 6 ).…”
Section: Introductionmentioning
confidence: 99%